Network structure of Turkish interbank market - Tuba Pelin Sümer; Süheyla Özyıldırım (Central Bank Review (CBR), 2022)
Global financial crisis has shown the importance of understanding the structure of interbank relations. In this study, we investigate the network relations based on interbank exposures in Türkiye. We estimate several network statistics and document how the network relations have changed over the time period of 2002-2021. We find that the network structures vary substantially by financial instruments such as repo, deposit, loan, security issuances, derivatives and other off-balance sheet items showing the significance of covering all type of exposures in network analysis. Using network statistics, we show that Turkish interbank network structure shows a core-periphery structure which is found to be more resilient during stress times in the literature. Finally, we find that larger banks are characterized as having higher network centrality measures as degree, clustering coefficient and closeness centrality showing the importance of these banks in terms of intermediation and substitutability.
Keywords: G21; L14; 330; Network analysis; Financial interconnectedness